2019
DOI: 10.1002/jrs.5593
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Raman scattering enhancement via particle‐waveguide coupling

Abstract: Surface-enhanced Raman scattering relies crucially on the formation of hot spots, which are usually difficult to fabricate and modulate. In this paper, the reverse symmetrical waveguide structure (RSW) is applied as the Raman scattering enhancement substrate, whereas gold nanoparticles are mixed with sample solution to achieve the effective coupling between localized surface plasmon (LSP) and the guided modes. Experimental results verify that the reverse symmetry results in a large penetration depth of the gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…For most cases, TRRS provided better results compared to nongated measurements, demonstrating its suitability for future space‐exploration missions. Kan et al [ 193 ] reported the enhancement of tunable Raman scattering by means of particle‐waveguide coupling. They found that the Raman enhancement could be effectively adjusted by tuning the coupling efficiency of the waveguide.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…For most cases, TRRS provided better results compared to nongated measurements, demonstrating its suitability for future space‐exploration missions. Kan et al [ 193 ] reported the enhancement of tunable Raman scattering by means of particle‐waveguide coupling. They found that the Raman enhancement could be effectively adjusted by tuning the coupling efficiency of the waveguide.…”
Section: Raman Techniques and Methodsmentioning
confidence: 99%
“…Owing to the high reflectivity of the metal layer, the dielectric material as cladding with a high refractive index, like a single-mode dielectric waveguide, is nonessential in MCW. Silicon dioxide, 73,[78][79][80][81] polymer film, 82 and some functional materials (such as porous material 83 and hydrogel 84 ) have been utilized as waveguide materials. For a porous structure waveguide, optimizing the porosity to obtain the best electric field enhancement effect may be a practical way.…”
Section: Metal Cladding Waveguidementioning
confidence: 99%
“…At the same time, the collection efficiency of Raman scattering light is improved by the efficient optical collection effect of waveguide. Therefore, the combination of reverse-symmetry waveguides [ 21 ], silicon nitride nanophotonic waveguides [ 22 ], optical fibers, etc., and SERS has been greatly developed. Among them, the optical fiber SERS probe combines the advantages of optical fiber dexterity, long-distance transmission and remote online.…”
Section: Introductionmentioning
confidence: 99%